Answered

Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Complete the square 3x^2+12x-1 show working

Sagot :

[tex]3x^2+12x-1\\\\a=3;\ b=12;\ c=-1\\\\\Delta=b^2-4ac\to\Delta=12^2-4\cdot3\cdot(-1)=144+12=156\\\\x=\frac{-b\pm\sqrt\Delta}{2a}\\\\\sqrt\Delta=\sqrt{156}=\sqrt{4\cdot39}=\sqrt4\cdot\sqrt{39}=2\sqrt{39}\\\\x=\frac{-12\pm2\sqrt{39}}{2\cdot3}=\frac{-6\pm\sqrt{39}}{3}\\\\3x^2+12x-1=3(x-\frac{-6-\sqrt{39}}{3})(x-\frac{-6+\sqrt{39}}{3})\\\\=\boxed{3(x+\frac{6+\sqrt{39}}{3})(x+\frac{6-\sqrt{39}}{3})}[/tex]